Inflammation Relates to Chronic Behavioral and Neurological Symptoms in Military Personnel with Traumatic Brain Injuries. Issue 7 (July 2017) - Devoto, Christina; Arcurio, Lindsay; Fetta, Joseph; Ley, Mary; Rodney, Tamar; Kanefsky, Rebekah; Gill, Jessica
Studies have shown that the presence of acute inflammation during recovery is indicative of poor outcomes after a traumatic brain injury (TBI); however, the role of chronic inflammation in predicting post-TBI-related symptoms remains poorly understood. The purpose of this study was to compare inflammatory biomarkers (tumor necrosis factor [TNF]-α, interleukin [IL]-6, and IL-10) in active duty personnel who either sustained or did not sustain a TBI. Service members were also assessed for post-traumatic stress disorder (PTSD), depression, and quality of life through self-reported measures. IL-6 and TNF-α concentrations were greater in the TBI group than in the control group. Of those with a TBI, IL-6 and TNF-α concentrations were greater in the high-PTSD group than the low-PTSD group. No significant differences were found in IL-10 or the IL-6/IL-10 ratios between those with low and high PTSD. Exploratory factor analysis was conducted to describe the latent structure of variables relating to emotional and physical health (i.e., Short Form 36 subcomponents, etc.) and their relationships within the TBI group with inflammatory cytokines. Four symptom profiles were found, with the third component most relating to PTSD and depression symptoms and high inflammation. This study indicates that the comorbidity of TBI and PTSD is associated with inflammation in a military sample, emphasizing the necessity for intervention in order to mitigate the risks associated with inflammation.